2002
DOI: 10.1038/sj.bmt.1703677
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome and quality of life of patients who are alive and in complete remission more than two years after allogeneic and syngeneic stem cell transplantation

Abstract: Summary:We assessed long-term outcome in 155 patients who had undergone an allogeneic/syngeneic stem cell transplant (SCT) and were in complete remission for more than 2 years after transplant. Probability of late transplantrelated mortality was 6%, and affected only patients with chronic graft-versus-host disease (cGVHD). Thirteen percent of patients experienced relapse. Overall survival projected at 10 and 15 years was 83% and 76%, respectively. Secondary malignancies occurred in two patients, 7.5 and 11 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
3
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 29 publications
3
71
3
1
Order By: Relevance
“…[12][13][14]19,20,46 We found that immunosuppressive therapy was another strong adverse factor, and it seemed have a larger impact on role/social QOL than GVHD. In this study, younger age was associated with a worse QOL especially in mental state, which is inconsistent with previous reports.…”
Section: Qol Estimates Provided By Patientsmentioning
confidence: 90%
See 1 more Smart Citation
“…[12][13][14]19,20,46 We found that immunosuppressive therapy was another strong adverse factor, and it seemed have a larger impact on role/social QOL than GVHD. In this study, younger age was associated with a worse QOL especially in mental state, which is inconsistent with previous reports.…”
Section: Qol Estimates Provided By Patientsmentioning
confidence: 90%
“…Many studies have been conducted to evaluate the QOL after allo-HCT. [12][13][14]19,20,[41][42][43][44][45][46][47] Several studies have compared the QOL between allo-HCT and chemotherapy groups. However, these results were conflicting, and few have controlled confounding backgrounds.…”
Section: Qol Estimates Provided By Patientsmentioning
confidence: 99%
“…The reliability and validity of the EORTC QLQ-C30 have been confirmed in previous studies. 11,13,20 High internal consistency and reliability has also been demonstrated in a BMT population. 6 The Leukaemia-BMT (QLQ-LEU) module was developed to evaluate the long-term sequelae of leukaemia treatments.…”
Section: Qol Assessmentmentioning
confidence: 98%
“…3 Most of the previous studies are cross-sectional in design, apply one of several available instruments and pool all patients transplanted for different diagnoses at a single centre. [4][5][6][7][8][9][10][11][12] Although marked morbidity in the first few years is evident, there is a clear trend to improved QoL in long-term survivors of transplantation. 6,8 Nonetheless, aggregated studies confirm that a minority of individuals continue to suffer from the effects of chronic graft-versus-host disease (GvHD) and sexual dysfunction.…”
Section: Allogeneic Sctmentioning
confidence: 99%
“…First, many studies combine results from auto-and allo-SCT patients, 18,19 which is not optimal because the quality-of-life scores 20 and RTW rates seems to differ significantly between those groups. 7,21 Second, occupational status before SCT is either unknown 8,14,17,[22][23][24] or gathered just before the SCT, 18,19,21 which is misleading because many patients at that time point are on sick leave because of consolidation treatments. Third, only those who worked before SCT are included most often in these studies.…”
Section: Introductionmentioning
confidence: 99%